Indonesian Geopolitics: Response to the Dynamics Occurring in the World - Kunkunrat, Kunkunrat (Journal of Economics and Business (JECOMBI), 2023)
In the context of globalization and rapid geopolitical changes, Indonesia as an archipelagic country with a strategic position has an increasingly important role in facing challenges and opportunities at the international level. This research aims to analyze and identify Indonesia's geopolitical response to the dynamics currently occurring in the world. The research method is descriptive qualitative, including literature analysis, secondary data, and interviews with geopolitical and diplomatic experts. By focusing on changes in dynamics that are occurring, such as the increasingly heated rivalry war between the United States and China, the Russia-Ukraine war, this research will explore the Indonesian government's strategy in dealing with these dynamics. The research results highlight that the volatile global political situation has had a significant impact on Indonesia's foreign policy. The link between global dynamics and Indonesia's national interests requires a careful approach. In conclusion, Indonesia needs to maintain a balance between national interests and participation in international cooperation, utilize strategic forums such as the G-20 to support national development, prioritize regional cooperation through ASEAN, optimize the potential of energy resources as a comparative advantage, and create political stability and security domestically as the main basis for facing the complexity of global geopolitical dynamics.